SISTEM INFORMASI E-PRESENSI SISWA MENGGUNAKAN QR CODE PADA MTS MA’ARIF NU ROUDLOTUL MUSTHOFA BERBASIS WEB - Raditiya Sholechan; Hari Lugis Purwanto; Gaguk Susanto (Department of System Information, 2023)
The attendance process for student attendance at MTs Ma'arif NU Roudlotul Muhofa has not been maximized. In the activity of filling in attendance using paper media, data invalidation often occurs because students can manipulate attendance at the madrasa. Therefore, attendance needs to be digitized to reduce fraud and invalidity of attendance data and simplify the attendance process. This application system is capable of carrying out attendance that is in accordance with manual attendance and can be used to replace the previous student attendance process which still uses plain paper. The development of this e-presence system uses the Waterfall development method. From the results of the research conducted, the results of a system capable of assisting presence activities and the results of the User Acceptance Test (UAT) that have been carried out have an average total result of 87.95%.